Desarrollo de un dispositivo portátil de seguridad para principiantes en el Gimnasio (2024)
In the realm of weightlifting and strength training, the use of lifting belt has been a commonly adopted tool, considered by many as an essential element to guarantee stability during the execution of various exercises. However, this accessory is not without controversy and concerns, especially when it comes to beginner users. This project is focuses on proposing an alternative device configuration to the belt, aimed at a group of beginner users in the world of weight lifting and training in gym.